2014
DOI: 10.1289/ehp.1307832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arsenic on Osteoblast Differentiation in Vitro and on Bone Mineral Density and Microstructure in Rats

Abstract: Background: Arsenic is a ubiquitous toxic element and is known to contaminate drinking water in many countries. Several epidemiological studies have shown that arsenic exposure augments the risk of bone disorders. However, the detailed effect and mechanism of inorganic arsenic on osteoblast differentiation of bone marrow stromal cells and bone loss still remain unclear.Objectives: We investigated the effects and mechanism of arsenic on osteoblast differentiation in vitro and evaluated bone mineral density (BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…Because phosphate is crucial for bone growth and mineralization (Penido and Alon 2012), lack of phosphate due to substitution by arsenic may have led to shorter height among the exposed participants. Indeed, arsenic may affect bone metabolism, as shown in experimental studies (Aybar Odstrcil et al 2010;Hu et al 2012;Szymczyk et al 2006;Wu et al 2014), and arsenic exposure inhibits endochondral ossification and osteoblast differentiation (Aybar Odstrcil et al 2010;Wu et al 2014). In humans, chronic exposure is associated with diminished bone mass density in adult males (Akbal et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because phosphate is crucial for bone growth and mineralization (Penido and Alon 2012), lack of phosphate due to substitution by arsenic may have led to shorter height among the exposed participants. Indeed, arsenic may affect bone metabolism, as shown in experimental studies (Aybar Odstrcil et al 2010;Hu et al 2012;Szymczyk et al 2006;Wu et al 2014), and arsenic exposure inhibits endochondral ossification and osteoblast differentiation (Aybar Odstrcil et al 2010;Wu et al 2014). In humans, chronic exposure is associated with diminished bone mass density in adult males (Akbal et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a prospective cohort study from Bangladesh suggests an inverse association between early-life arsenic exposure from contaminated drinking water and children's growth during infancy (Gardner et al 2013;Saha et al 2012). Growth inhibition due to arsenic exposure has been supported by laboratory animal studies that show decreased body length and femur length (Hu et al 2012), as well as decreased bone mass density (Wu et al 2014). A cross-sectional study of adult males reported an inverse association between environmental arsenic exposure and bone mass density (Akbal et al 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Little evidence exists on how iAs exposure impacts osteogenesis, however, other arsenical compounds such as arsenic trioxide decrease osteogenesis in bone marrow stromal cells following exposure (Wu et al, 2014), which suggests these differentiation processes may be influenced by environmental contaminants such as iAs. Interestingly, unlike adipogenesis, osteogenesis, and chondrogenesis showed a strikingly similar response to increasing iAs concentrations, showing a concentration-dependent decrease in the expression of several differentiation markers.…”
Section: Discussionmentioning
confidence: 99%
“…This was partly due to a host of evidence cumulating in arsenic being designated as a Group 1 carcinogen by the International Agency for Research on Cancer (IARC, 2012), which suggested that exposure was directly linked to the risk of developing cancer within humans. However, iAs also has been shown to play a role in the dysfunction of regenerative capacity in muscles (Ambrosio et al, 2014) and bone (Wu et al, 2014), suggesting detrimental effects on stem/progenitor cell populations in these tissues.…”
mentioning
confidence: 99%